Research on the Problems and Countermeasures of the Ideological and Political Theory Courses and Values Throughout the Curriculum Collaborative Construction in Higher Vocational Colleges (Journal of Global Humanities and Social Sciences, 2024)
Higher vocational universities are important bases for the training of technical and skilled personnel, as well as important places for values education. How to combine ideological and political education and specialized education well is a difficult problem faced by the current higher vocational education. This paper discusses the existing problems in the collaborative construction of ideological and political courses in higher vocational universities and the values throughout the curriculum from the perspectives of teaching content, teaching methods, and teaching objectives, and proposes corresponding countermeasures, hoping to provide some reference for promoting the quality improvement of ideological and political education in higher vocational colleges.